Vernier-templated synthesis, crystal structure, and supramolecular chemistry of a 12-Porphyrin nanoring - Kondratuk, Dmitry V.; Sprafke, Johannes K.; O'Sullivan, Melanie C.; Perdigão, Luis M.A.; Saywell, Alexander; Malfois, Marc; O'Shea, James N.; Beton, Peter H.; Thompson, Amber L.; Anderson, Harry L. (Wiley-VCH Verlag, 2014)
Vernier templating exploits a mismatch between the number of binding sites in a template and a reactant to direct the formation of a product that is large enough to bind several template units. Here, we present a detailed study of the Vernier-templated synthesis of a 12-porphyrin nanoring. NMR and small-angle X-ray scattering (SAXS) analyses show that Vernier complexes are formed as intermediates in the cyclo-oligomerization reaction. UV/Vis/NIR titrations show that the three-component assembly of the 12-porphyrin nanoring figure-of-eight template complex displays high allosteric cooperativity and chelate cooperativity. This nanoring–template 1:2 complex is among the largest synthetic molecules to have been characterized by single-crystal analysis. It crystallizes as a racemate, with an angle of 27° between the planes of the two template units. The crystal structure reveals many unexpected intramolecular C[BOND]H⋅⋅⋅N contacts involving the tert-butyl side chains. Scanning tunneling microscopy (STM) experiments show that molecules of the 12-porphyrin template complex can remain intact on the gold surface, although the majority of the material unfolds into the free nanoring during electrospray deposition.